2019
DOI: 10.1002/mar.21307
|View full text |Cite
|
Sign up to set email alerts
|

The effect of signage and emotions on satisfaction with the servicescape: An empirical investigation in a healthcare service setting

Abstract: Marketing and environmental psychology studies have long emphasized the importance of signage in large and dispersive service settings but have focused little on utilitarian service contexts. Previous studies have also analyzed the role of emotions in customer satisfaction with the servicescape, particularly in hedonic service environments such as malls, hotels, and restaurants, but a limited research has been conducted on the role of emotions in utilitarian service settings such as healthcare services. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 87 publications
(109 reference statements)
0
13
0
Order By: Relevance
“…This is mainly because at every step of the service process, online and offline operators can put themselves in the position of thinking for the customers, so as to facilitate the customer benefits (Ashok et al, 2018). Vigolo et al (2020) found signage has a positive and significant effect on service satisfaction with the servicescape in the healthcare services. In this study, CS has a fully mediating effect on the PSQ and PI.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…This is mainly because at every step of the service process, online and offline operators can put themselves in the position of thinking for the customers, so as to facilitate the customer benefits (Ashok et al, 2018). Vigolo et al (2020) found signage has a positive and significant effect on service satisfaction with the servicescape in the healthcare services. In this study, CS has a fully mediating effect on the PSQ and PI.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Like in cruise tourism attributes like d ecor, natural scenery, the onboard environment was found important (Lyu et al, 2017). For instance, in a healthcare service setting a significant effect of signage on satisfaction with servicescape has been found positive (Vigolo et al, 2020). One of the studies done by Grosso et al (2018) suggested that in retailing, the store environment should be aligned with the positioning of the retail store by creating an encouraging atmosphere and a pleasing in-store experience that intensifies customer satisfaction.…”
Section: Literature Review 21 Servicescapementioning
confidence: 99%
“…For example, environmental elements such as signage, art, plants and greenery are associated with patient satisfaction and well-being (Hamed et al. , 2019; Vigolo et al. , 2020).…”
Section: Conceptual Backgroundmentioning
confidence: 99%